Case Report: Use of endobronchial Watanabe spigot and coagulation factor XIII supplementation in the treatment of persistent pneumothorax due to pneumocystis pneumonia with human immunodeficiency virus infection - Katsumasa Koyama; Daisuke Minami; Hayato Isobe; Ryo Shirai; Niro Okimoto; Koichi Tomoda (Frontiers in Medicine, 2022)
Pneumocystis jiroveceii pneumonia is one of the most common opportunistic infections associated with human immunodeficiency virus. Endobronchial Watanabe spigot has been recommended for refractory pneumothorax, even with persistant air leak despite continuous negative pressure control via thoracic drainage. Moreover, coagulation factor XIII is considered effective in wound healing.